An E280K Missense Variant in KCND3/Kv4.3—Case Report and Functional Characterization - Ågren, Richard; Geerdink, Niels; Brunner, Han G.; Paucar, Martin; Kamsteeg, Erik-Jan; Sahlholm, Kristoffer (International journal of molecular sciences, 2023)
A five-year-old girl presented with headache attacks, clumsiness, and a history of transient gait disturbances. She and her father, mother, twin sister, and brother underwent neurological evaluation, neuroimaging, and exome sequencing covering 357 genes associated with movement disorders. Sequencing revealed the new variant KCND3 c.838G>A, p.E280K in the father and sisters, but not in the mother and brother. KCND3 encodes voltage-gated potassium channel D3 (Kv4.3) and mutations have been associated with spinocerebellar ataxia type 19/22 (SCA19/22) and cardiac arrhythmias. SCA19/22 is characterized by ataxia, Parkinsonism, peripheral neuropathy, and sometimes, intellectual disability. Neuroimaging, EEG, and ECG were unremarkable. Mild developmental delay with impaired fluid reasoning was observed in both sisters, but not in the brother. None of the family members demonstrated ataxia or parkinsonism. In Xenopus oocyte electrophysiology experiments, E280K was associated with a rightward shift in the Kv4.3 voltage-activation relationship of 11 mV for WT/E280K and +17 mV for E280K/E280K relative to WT/WT. Steady-state inactivation was similarly right-shifted. Maximal peak current amplitudes were similar for WT/WT, WT/E280K, and E280K/E280K. Our data indicate that Kv4.3 E280K affects channel activation and inactivation and is associated with developmental delay. However, E280K appears to be relatively benign considering it does not result in overt ataxia.